RESEARCH ON RIBA IN ISLAM AND THE TREND OF CHOICE - Munadi Munadi (ADISAM Publisher, 2022)
The purpose of this study is to discuss Riba in an economic system, especially a conventional economic system. The view of the general public who still considers that the conventional bank banking system and Islamic banking are the same and there is no difference, between interest and profit sharing are the same. The interest offered by conventional banking which is more definitely calculated attracts the interest of the Muslim community, rather than the profit sharing system that exists in the Syrian banking. Besides, the blessings of rizki and halalness are not the main measure in transactions in Islamic banking. Halal and haram are no longer the main goal in seeking sustenance. This view has always been the background. Socio- economics always tends to adopt various attitudes and actions of usury. Even though the community understands and understands the possible impact of usury loans, the fact is that moneylenders are still an option.